2014
DOI: 10.1111/1462-2920.12543
|View full text |Cite
|
Sign up to set email alerts
|

The nitrogen cycle in cryoconites: naturally occurring nitrification‐denitrification granules on a glacier

Abstract: Cryoconites are microbial aggregates commonly found on glacier surfaces where they tend to take spherical, granular forms. While it has been postulated that the microbes in cryoconite granules play an important role in glacier ecosystems, information on their community structure is still limited, and their functions remain unclear. Here, we present evidence for the occurrence of nitrogen cycling in cryoconite granules on a glacier in Central Asia. We detected marker genes for nitrogen fixation, nitrification a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(74 citation statements)
references
References 68 publications
12
62
0
Order By: Relevance
“…We found that N cycling functional gene abundances increased with time, which was in agreement with previous research in Tianshan Mountain No.1 glacier, showing that N cycling functional gene abundances increased along the chronosequence (Segawa et al, 2014). However, Brankatschk et al (2011) showed that ammonia oxidizing microbial community abundances increased with time, but denitrifying bacterial ( nirK/S and nosZ ) gene abundances decreased in the Damma Glacier forefield.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that N cycling functional gene abundances increased with time, which was in agreement with previous research in Tianshan Mountain No.1 glacier, showing that N cycling functional gene abundances increased along the chronosequence (Segawa et al, 2014). However, Brankatschk et al (2011) showed that ammonia oxidizing microbial community abundances increased with time, but denitrifying bacterial ( nirK/S and nosZ ) gene abundances decreased in the Damma Glacier forefield.…”
Section: Discussionsupporting
confidence: 92%
“…Segawa et al (2014) found isotope ratio evidence of the occurrence of nitrification on the surface of the Tianshan Mountain No.1 glacier. Past research indicated that in the glacier foreland ecosystem the ammonia-oxidizing process was mainly driven by AOA, due to the AOA having a better adaptability to the ammonia-poor environment and lower pH than AOB (Di et al, 2009; Ollivier et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…High abundance of cyanobacteria has been already observed in polar and alpine cryoconite (Segawa et al, 2014;Stibal et al, 2014), whereas low abundance was reported on Rotmoosferner Glacier (Tirol, Austria; Edwards et al, 2013). Consistently, coverage of psbD (photosystem II P680 reaction center D2 protein gene) was (mean ± s.e.)…”
mentioning
confidence: 58%
“…In several other environments, such phenomena have been explained by anoxic microhabitats, created by biofilm formation and oxygen depletion by aerobes [8]. Indeed, denitrification processes were detected in cryoconite granules that were less than 2 mm in diameter, where Polaromonas cells have been proposed as O 2 scavengers and extracellular polymer producers, causing clumping of the sediment [26]. Polaromonas spp.…”
Section: Discussionmentioning
confidence: 99%